2004
DOI: 10.1152/ajpendo.00189.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in the responsiveness of cardiac and skeletal muscle to fatty acids

Abstract: Cardiac and skeletal muscle both respond to elevated fatty acid availability by increasing fatty acid oxidation, an effect mediated in large part by peroxisome proliferator-activated receptor-alpha (PPAR alpha). We hypothesized that cardiac and skeletal muscle alter their responsiveness to fatty acids over the course of the day, allowing optimal adaptation when availability of this substrate increases. In the current study, pyruvate dehydrogenase kinase 4 (pdk4) was utilized as a representative PPAR alpha-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 26 publications
(28 reference statements)
9
103
1
2
Order By: Relevance
“…In nocturnal rats for instance, LPL activity increases during the dark period in adipose tissue (i.e., leading to accelerated fat accumulation), while its activity increases during the light period in the skeletal muscles (i.e., to support increased fat uptake and oxidation) (Tsutsumi et al, 2002). Circulating levels of FFA show an elevation during the light period (i.e., during fasting) and decline during the dark period (i.e., during feeding) in nocturnal rats and mice Stavinoha et al, 2004;Tsutsumi et al, 2002). Abrogation of the daily plasma FFA rhythm in rats with a bilaterally ablated SCN indicates the involvement of the central clock in daily changes in plasma FFA (Yamamoto et al, 1987).…”
Section: Daily Rhythms Of Lipid Metabolismmentioning
confidence: 99%
“…In nocturnal rats for instance, LPL activity increases during the dark period in adipose tissue (i.e., leading to accelerated fat accumulation), while its activity increases during the light period in the skeletal muscles (i.e., to support increased fat uptake and oxidation) (Tsutsumi et al, 2002). Circulating levels of FFA show an elevation during the light period (i.e., during fasting) and decline during the dark period (i.e., during feeding) in nocturnal rats and mice Stavinoha et al, 2004;Tsutsumi et al, 2002). Abrogation of the daily plasma FFA rhythm in rats with a bilaterally ablated SCN indicates the involvement of the central clock in daily changes in plasma FFA (Yamamoto et al, 1987).…”
Section: Daily Rhythms Of Lipid Metabolismmentioning
confidence: 99%
“…Taqman assays used in this study are presented in the Table in the online-only Data Supplement or have been reported previously. [17][18][19][20] All gene expression data are normalized to the housekeeping gene cyclophilin, which did not differ between the groups investigated (data not shown).…”
Section: Activity and Malonyl Coenzyme A Measurementsmentioning
confidence: 99%
“…7 Therefore, we hypothesized that long-term MCD inhibition in the mcd Ϫ/Ϫ mouse heart may lead to compensatory alterations in the expression of metabolic genes involved in fatty acid oxidation and glucose oxidation. This includes CD36, which is involved in fatty acid transport; uncoupling protein 3 (UCP3), mitochondrial thioesterase 1 (MTE1), and CPT1, which are associated with increased fatty acid oxidation 15,17,19,21,22 ; and pyruvate dehydrogenase kinase-4 (PDK-4), 18 which is one isoform of the family of kinases responsible for phosphorylating and inhibiting the pyruvate dehydrogenase complex, thus decreasing glucose oxidation. 23 We therefore measured expression of these various metabolic genes and found that expressions of cd36, ucp3, mte1, and cpt1 were increased in mcd Ϫ/Ϫ mouse hearts compared with wild-types (Figure 4a to 4d).…”
Section: Dyck Et Al Reduced Ischemic Injury In MCD Ko Mouse Heartsmentioning
confidence: 99%
“…The adipokine, adiponectin, which plays an important role in insulin sensitivity, inflammation and fatty acid oxidation, presents a circadian rhythm similar to insulin, with peak levels in the early active phase and low levels in the inactive phase ( Table 2). The early hours of the active phase are characterized by higher glucose levels and thus higher insulin demand in anticipation of the onset of stimulus [88][89][90]. At the end of the active phase and the start of the rest phase, insulin levels and sensitivity are low and oral or intravenous glucose (or consumption of a meal) leads to a significantly higher plasma glucose response.…”
Section: The Circadian Clock In Animal Models Of Insulin Resistance Amentioning
confidence: 99%
“…Accordingly, rodents respond differently by day and night to insulin and 2-deoxy-D-glucose with a rapid fall in blood glucose levels occurring at the end of the active phase after a 6h overnight fast in contrast to delayed and diminished hypoglycemia following a day time (inactive phase) fast [89]. Furthermore, the circulating FFA levels follow the same circadian pattern as glucose and are low in the active phase and high in the inactive phase in both humans and rats, with an increased turnover present in humans with T2D [90,91]. The role of adiponectin in FFA, insulin and glucose metabolism in context of the circadian rhythm is shown in Figure 7.…”
Section: The Circadian Clock In Animal Models Of Insulin Resistance Amentioning
confidence: 99%